Sediment yield in Paraopeba River Basin – MG, Brazil. Issue 4 (1st October 2016) - Duraes, Matheus Fonseca; de Mello, Carlos Rogério; Beskow, Samuel
ABSTRACT: Sediment delivery rate (SDR) is traditionally defined as a fraction of upland gross erosion that is transported through the outlet of a given basin, thus representing an index of the sediment transport efficiency. The objective of this study was to evaluate a model-based approach for SDR determination in the Paraopeba River Basin (PRB), located at the central region of Minas Gerais State, Southeastern Brazil. The empirical model known as RUSLE, which stands for Revised Universal Loss Equation, was used embedded in a geographical information system (GIS) to estimate the soil erosion potential. Based on a monitoring network, considering the period between 1997 and 2008, the sediment transport was determined in five sub-basins of the PRB. The average water erosion for PRB was 2.7 ton ha −1 yr −1, while the sediment transport varied from 0.25 to 1.63 ton ha −1 yr −1 . Considering the area and the slope as the independent variables, three empirical models were applied for estimating SDR. The results showed adequate fit for the proposed model, resulting in improvements for SDR estimates in PRB. On evaluating only sub-basins, the observed average SDR was 0.38, while the corresponding estimated value was 0.37. It was found that the three traditional equations did not generate acceptable results and this can be explained by the overestimation of SDR values for PRB.